SOCIAL CONSTRUCTION OF POWERFUL WOMEN TO FIGHT AGAINST CRIMINAL ACTS IN PHILIP NOYCE'S SALT MOVIE (2010):A FEMINIST APPROACH - HERAWATI, NONA (2011)
The major problem of this study is to reveal how the social construction of powerful women to fight against criminal acts is reflected in Philip Noyce Jane Salt. The objective of this study is to analyze the movie based on its structural elements and a feminist approach. In analysis, the writer uses qualitative method. The object of the study is Philip Noyce Salt released in 2010 in the United State of America. The data sources consist of primary and secondary data sources. The primary data source is Salt movie itself and the secondary data sources are the other sources related to the primary data such as the information about the director's biography, websites, and the historical background of America in the early of twenty first century. The method of the data collection are watching the movie, taking notes the important data, identifying the topic, capturing scene, determining the major character, and the last arranging the data based on category of elements of literature review. The technique of data analysis is descriptive analysis. The outcome of the study is shown in the following conclusion. First, from the structural analysis of the movie shows Philip Noyce wants to convey a message that a woman is just as powerful as man is. The second, based on Feminist Approach, this movie contains many facts that are revealed by Philip Noyce which reflect physical equality, female power and heroism. In this movie, Philip Noyce wants to say that a woman is not a weak person.